(untitled) (Journal of International Studies, 2020)
This study examines the role of tacit knowledge in the knowledge acquisition process among international strategic alliances firms in Malaysia. The significance of tacit knowledge is discussed and the effectiveness in acquiring the tacit knowledge is analysed. Tacit knowledge plays a vital role in the knowledge acquisition process as it is very important and harder to be acquired compared to explicit knowledge. Two major issues related to the tacitness of knowledge in the knowledge acquisition process are learning capacity and accessibility. Learning capacity and accessibility were examined through personal interviews with 41 Malaysian firms that engaged in international strategic alliances. Data obtained were qualitatively analysed. This study found that Malaysian firms highly depend on foreign partners particularly on the technical knowledge though the relationship has been established for quite some time. Despite creating efforts to reduce the dependency, the reliance on the foreign firms remains high and learning process is rather slow. In accessing the knowledge from the foreign partner, local firms have to deal with eight major challenges and problems. These challenges have limited the local firms ability to learn and acquire more knowledge from the foreign partner. Trust, which closely related to the accessibility, is proved to influence the level of knowledge acquired. A higher degree of trust will ease the process of knowledge acquisition while a lower degree of trust acts vice versa. Therefore, it is essential for the local firms to develop a trust in their international strategic alliances relationship.